PELAKSANAAN ASESSMEN DIAGNOSTIK NON-KOGNITIF DALAM RANGKA MEMEMETAKAN KEBUTUHAN BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN BAHASA BALI KELAS X TSM SMK PGRI 6 DENPASAR TAHUN AJARAN 2023/2024 - Kadek Dedy Herawan (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2024)
Assessment is an integrated part of the teacher's learning process. Assessment can facilitate learning and provide complete information as feedback for teachers, students, and parents so that they can find out the results of the goals set and can guide determining strategies, approaches, techniques, and methods in the subsequent learning process. Currently, there are still many educators who have not mapped the learning needs of their students, so many students experience bias in achieving their learning goals. SMK PGRI 6 Denpasar, which has Implemented the Independent Change Curriculum Implementation, has directed its educators to first map the needs of their students before starting teaching. In this research, to map students' learning needs in learning Balinese, especially in class The results obtained were that students' learning needs based on interests and talents were in good condition, and students' learning needs based on learning styles were found to be varied, namely, 6 people needed a visual learning style, 17 people needed an auditory learning style, and 3 people needed a kinetic learning style. Based on the results of the non-cognitive diagnostic assessment analysis, Balinese language teachers have made learning preparation plans, process plans, content plans, and ongoing evaluation steps Keywords: Diagnostic assessment, non-cognitive diagnostics, student learning needs